The Role of the Kidneys in the Regulation of Blood Pressure (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The kidneys play a crucial role in the regulation of blood pressure through several mechanisms, including the renin-angiotensin-aldosterone system (RAAS), the regulation of sodium and water balance, and the modulation of vascular resistance. This article explores the multifaceted functions of the kidneys in maintaining hemodynamic stability, the pathophysiological implications of renal dysfunction on blood pressure, and the therapeutic approaches targeting kidney function to manage hypertension. Understanding these relationships is vital for developing effective treatment strategies for hypertension and related cardiovascular diseases.